In‐syringe ionic liquid‐dispersive liquid–liquid microextraction coupled with HPLC for the determination of trans, trans‐muconic acid in human urine sample. Issue 16 (25th June 2021) - Abbaszadeh, Sepideh; Yousefinejad, Saeed; Jafari, Saeed; Soleimani, Esmaeel
Abstract: trans, trans‐Muconic acid has been widely used as a biomarker in biological monitoring of benzene‐exposed workers during routine occupational health services. In the present study, a novel microextraction technique, in‐syringe ionic liquid‐dispersive liquid–liquid microextraction, was implemented for preconcentration of trans, trans‐muconic acid followed by analytical determination by high‐performance liquid chromatography with ultraviolet detection. Moreover, the important variables affecting the performance of applied microextraction technique including needle diameter, volume of the spiked sample, volume of the ionic liquid, salt addition, rotation speed of centrifugation, centrifuge time, and ultrasonic time were optimized by experimental design. A good linear relationship was observed at the range of 0.032–10 μg/mL between the peak area and the concentration levels ( R 2 = 0.9997). The limit of detection and extraction recovery for trans, trans‐muconic acid were 0.011 μg/mL and >96.2%, respectively. This method provided easy and rapid analysis of low amounts of trans, trans‐muconic acid in human urine with simple equipment.